Cover Picture: Topological Polymer Chemistry Enters Surface Science: Linear versus Cyclic Polymer Brushes (Angew. Chem. Int. Ed. 50/2016). Issue 50 (28th October 2016) - Morgese, Giulia; Trachsel, Lucca; Romio, Matteo; Divandari, Mohammad; Ramakrishna, Shivaprakash N.; Benetti, Edmondo M.
Abstract : Topological effects by cyclic polymers are enhanced in the confinement of a surface. In their Communication onpage 15583 ff., E. M. Benetti et al. show that cyclic polyoxazoline brushes provide higher steric stabilization with respect to their linear analogues and display superlubricious behavior in water. Topological polymer chemistry enters surface science and reveals results that seem to confirm Wolfgang Pauli's famous statement: "God made the bulk; the surface was invented by the devil."